Chinese massage manual a comprehensive, step-by-step guide to the healing art of Tui Na - Pritchard, Sarah (Piatkus, 1999)
Featuring step-by-step photographs, this text provides an overview of traditional Chinese medicine, showing how Tui Na works in conjunction with oriental diagnosis, yin/yang and five element theory, and the body's energy points.